Modern international economics - Ethier, Wilfred J. (W. W. Norton, 1995)
This book is divided into seven parts: Why nations trade; How nations trade; Using trade theory; Monetary mechanics; International monetary economics; Open-economiy macroeconomics; and The modern international economy.